2012
DOI: 10.1007/s00464-012-2618-4
|View full text |Cite
|
Sign up to set email alerts
|

Predictive risk factors of perforation in gastric endoscopic submucosal dissection for early gastric cancer: a large, multicenter study

Abstract: The result of this study demonstrated that the location of the lesion (body) and piecemeal resection were related to perforation during ESD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…Additionally, in the control group, proximal gastric lesions were noted to be more challenging, consistent with clinical experience. 24,25 However, when using the suture-pulley method, there was no difference in resection time or degree of difficulty with regard to lesion location. This suggests that the suture-pulley method may make the more complicated ESDs more feasible, in addition to making more straightforward ESDs more efficient.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in the control group, proximal gastric lesions were noted to be more challenging, consistent with clinical experience. 24,25 However, when using the suture-pulley method, there was no difference in resection time or degree of difficulty with regard to lesion location. This suggests that the suture-pulley method may make the more complicated ESDs more feasible, in addition to making more straightforward ESDs more efficient.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported the upper-third location as associated with a higher rate of perforation during ESD [3, 68, 21]. In terms of bleeding, Oda et al reported that rates of significant immediate bleeding are higher in the upper and middle thirds of the stomach than in the lower third because of the larger diameter of the submucosal arteries in the upper and middle thirds [3, 4, 22].…”
Section: Discussionmentioning
confidence: 99%
“…Although most perforations are managed through conservative treatment with endoscopic closure, surgery is needed in 2.5~3.3% of patients with perforation [1214]. Previous studies reported that the upper area of the stomach, piecemeal resection, and long procedure times were risk factors associated with perforation after ESD [1316, 20].…”
Section: Discussionmentioning
confidence: 99%
“…Iatrogenic perforations induced by gastric ESD and EMR have been reported to occur in approximately 4% and 1% of cases, respectively [10, 11]. Most perforations can be managed through endoscopic closure and conservative treatment, but surgery is required in rare cases [1214]. A delay in deciding to perform surgery may cause fatal clinical outcomes in some patients.…”
Section: Introductionmentioning
confidence: 99%